Unsur Pendukung Penciptaan Kesenian Yaksa Brajadenta Versi Dramatari Karya Kelompok Paguyuban Mekarsari - Kawuryansih Widowati (FBS Padang State University, 2023)
This study aims to describe the description of the forms and elements that influence the creation of the dance drama version of the Yaksa Brajadenta art. This research uses a qualitative descriptive method with data collection techniques which include observation, interviews, and documentation. The results of the study show that the Yaksa Brajadenta art is one of the products of artistic innovation which is the pride of the people of Wonodoyo Village. This art is realized because there are four elements that influence each other. The first is the genius factor, namely the ability of local residents to learn art on an autodidact basis. The second is resources, namely the source of the materials used to make works of art in the form of wayang stories, ritual life in the village, as well as the form of rampak buta dance. The third is need which includes the group's internal needs and market competition. The fourth is opportunity which includes the opportunity to practice and learn various kinds of arts from other forms and regions. Of the four elements, it is known that if one of the elements is not fulfilled then this art will not be realized.